Rosella (Hibiscus sabdariffa L.) extract lip balm: optimization of the composition of beeswax and paraffin wax as a base - Tusilowati, Defita Andri; Sugihartini, Nining (Journal of Halal Science and Research, 2023)
One of the main components of lip balm is wax. The wax content in the lip balm works to improve the consistency. In this study, a lip balm was prepared to contain rosella flower extract (Hibiscus sabdariffa L.), which contains anthocyanin and can be used as a natural dye. This study aimed to determine the effect of the combination of beeswax and paraffin wax as a wax base on the physical properties and physical stability of lip balm containing rosella flower extract (Hibiscus sabdariffa L.) so that the optimum composition can be obtained. Rosella flower extract (Hibiscus sabdariffa L.) was prepared by maceration method using 96% ethanol. The extract was formulated in eight formulas with variations of beeswax-paraffin wax and evaluated for physical properties (organoleptic, pH, melting point) and physical stability (organoleptic, pH every week). The optimum formula was obtained using a Simplex lattice design (SLD) with the help of Design-Expert® 10.0.1 software. The results of the simplex evaluation test using the one sample t-test at a 95% confidence level indicate that beeswax has a dominant influence in influencing pH and decreasing pH with design expert coefficient values of 2.09 and 0.50. Meanwhile, paraffin wax has a dominant influence on the melting point with a design expert coefficient value of 0.89. The composition of the two waxes did not affect the shape, texture, color, and scent based on organoleptic observations. The optimum formula for combining beeswax and paraffin wax is 8.02% and 12.31% to produce a product with a pH of 3.91, a melting point of 65.51ºC, and the ability to maintain the pH for four weeks.